Jubilee : God's answer to poverty? - Swithinbank, Hannah; Murangira, Emmanuel; Murray, Caitlin, 1984- (Regnum studies in mission., 2020)
What is Jubilee? How could it transform our understanding of the world today -- and of how God calls us to live in it? At the heart of Old Testament law is a revolutionary concept that, if applied today, could transform our economy and world. Jesus himself claimed that his ministry would bring its fulfilment, transforming the world. Uniting social justice, creation care, equality and worship, jubilee remains a radical challenge, thousands of years later. This exciting collection engages with this challenge and offers ideas and inspiration for disciples today. It brings together rigorous theological thought and practical experience from voices from around the world. Its chapters reflect on issues of poverty in its different dimensions and discuss some of the challenges that face churches, Christian organisations and individual Christians in responding to them. The authors each bring their unique context and perspectives which challenge us to go beyond viewing the jubilee ordinances as simple rules and help us to begin to understand the redemptive and restorative power of the jubilee principles for us today.